The New Frontier of Antisemitism: Racial Discourse and Oromo Extremism in Ethiopia - Berhanu, Girma (Advances in Social Sciences Research Journal, 2023)
Ethiopia is in dire straits due to a peculiarly malignant state system called Ethnic Federalism. In existence since the early 1990s, it has been sold as a brave attempt at empowering subjugated nationalities and, to borrow the Marxist parlance of the government that introduced it, ‘to let nations, nationalities and people’s blossom’.